Decomposition and minéralisation effect of various sources of pig manure on water quality and nutrients availability for agro-fish system in Benin - BOKOSSA, JANVIER KOUESSIVI HERVE; SAIDOU, A.; SOSSOUKPE, EDMOND; FIOGBE, EMILE DIDIER; KOSSOU, K. DANSOU (My University, 2014)
manure in improving the health of ecosystems, little is known about the biochemical mechanisms affecting the availability of nutrients released from the organic fertilizer in water. A litter bag study during 6 weeks was carried out in pots containing 25 liters of water with 15 g of pig dejections as organic fertilizers. The experimental design was a completely randomized block design with three replications. The treatments consisted of dejections of pigs nourished with: recommended diet composition T1, partially improved diet with Azolla filiculoides T2, improved diet with Azolla filiculoides T3, improved diet with cereal bran T4. A control treatment without dejection (T0) was considered in the study for comparison purpose. Four pigs per type of diet were considered leading to 16 white landrace pigs of six months age followed for dejection collections. Strong release of nutrients for better yield for agro-fish system was obtained in the manure T1 with 3 NO− (10.85 ± 0.00) mg/L; 2 NO− ( 0.011 ± 0.00) mg/L; 4 PO3− (2.13 ± 0.07) mg/L and K+ (10.76 ± 0.57) mg/L; Ca2+ (2.92 ± 0.11) mg/L and Mg2+ (2.53 ± 0.00) mg/L followed by manure T3 and T4 with high N content. The relatively low ratio C/N (14.25) for T1 and (15.84) for T3 induced more nutrients releasing. This study showed an important N loss probably due to microorganism activities which fluctuate nutrient availability. Also significant correlations were noted between the nutrient dynamics in water and physicochemical parameters showing the effect of abiotic factors on organic matter decomposition and mineralization which depend on microbial activities in water and pig manure composition.
Keywords: Pig’s Diet; Manure; Fertilization; Physico-Chemical Microbial Water Properties; Nutrients; Availability